Depression, anxiety in adolescents with exogenous obesity and depression, anxiety, caregiver burden, and burnout in their mothers - Celiloğlu, Can; Turan, İhsan and Ray, Perihan Çam and Özdemir Dilek, Semine and Çay, Mevra and Çelebi, Şükriye Tuğçe and Çimen, Ayşe Merve and Namlı, Zeynep and Yüksel, Bilgin (Frontiers in Pediatrics, 2025)
IntroductionThe development of obesity is associated with various biological, environmental, and psychological factors, and there is a bidirectional interaction between obesity and psychological health. Several reports have highlighted the intrafamilial transmission of psychopathologies among individuals with obesity. This study aimed to assess symptoms of depression and anxiety in adolescents with exogenous obesity and their mothers, along with maternal caregiver burden and burnout levels.MethodsAdolescents diagnosed with exogenous obesity and their mothers were prospectively enrolled in the study. Clinical data were recorded, and participants completed standardized assessment tools: children filled out the Screen for Child Anxiety Related Emotional Disorders (SCARED) and the Kovacs Children's Depression Inventory (CDI), while mothers completed the Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), Maslach Burnout Inventory (MBI), and Zarit Caregiver Burden Scale. Results were compared with those of a control group.ResultsA total of 49 obese adolescents (aged 12–18) and their mothers, and 43 age- and sex-matched controls with their mothers, were evaluated. The mean BMI of the obesity group was 35.29 ± 4.77 kg/m2 (BMI-SDS: 2.44 ± 0.40). No significant differences were observed between adolescents with obesity and control subjects regarding depression and anxiety scores. Similarly, mothers’ depression, anxiety, and caregiver burden scores did not significantly differ. However, emotional exhaustion and depersonalization subscale scores on the MBI were significantly higher among mothers of adolescents with obesity.DiscussionAll adolescents showed elevated depression and anxiety scores compared to national averages, regardless of obesity status. Levels of emotional exhaustion and depersonalization were significantly elevated in mothers of adolescents with obesity. Assessing maternal burnout may contribute to more effective management of childhood obesity.